Executive remuneration, performance and responsible governance in Morocco: empirical insights from a national governance barometer - Abderrahim CHTAOUI; Fatima Ezzahra BELFATMI; HAJJI Zouhair (International Journal of Scientific Research and Innovative Studies, 2026)
In emerging markets, studying the link between executive remuneration and performance remains challenging when published information is incomplete, inconsistent and rarely comparable across companies. Drawing on the 2025 edition (2024 data) of the Responsible Governance Barometer in Morocco, this article offers a secondary empirical analysis of a public dataset covering 92 publicly listed companies and over 100 data points per company. The methodology involves the systematic extraction of published indicators, their grouping into analytical dimensions consistent with the literature – board structure, ownership and control, specialised committees, board functioning, remuneration transparency and dissemination of CSR data – followed by their interpretation in the light of agency theory, managerial power theory and institutionalism. The results show that Moroccan corporate governance is more formalised than before, with boards averaging 9.4 members, 36% of structures separating executive and supervisory functions, 23% independent directors and 29% women. They also reveal a persistent gap between formal structure and substantive transparency: 53% of companies disclose executive remuneration, 70% disclose directors’ fees, and only 1% incorporate CSR or non-financial criteria into their remuneration policy. The article concludes that the Barometer provides a robust observatory of the institutional conditions in which the alignment of remuneration and performance can be assessed, without, however, providing, on its own, a sufficient basis for testing it econometrically at the firm level. Keywords Executive remuneration; corporate governance; performance; transparency; responsible governance; publicly listed companies; Morocco Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/610